Redistributive Promises and the Adoption of Economic Reform - Jain, Sanjay; Mukand, Sharun W (American Economic Review, 2003)
This paper analyzes the relationship between economic reform and the democratic process to ask the following question: Does the likelihood of adoption of an economic reform increase with an increase in the efficiency benefits from that reform? A priori we might expect that this likelihood should increase monotonically, for two reasons. First, economic reform results in an increase in the size of the national pie. If the government has the ability to make compensatory tax-transfers, an increase in each citizen's income is possible. Second, a larger economic reform results in a greater number of winners. This might also be expected to reinforce the political support for economic reform. So we should expect a reform with greater efficiency benefits to a larger population to have a greater chance of adoption by the government. However, in this paper we show that this intuition is mistaken. In particular, we demonstrate that there exists a certain non-monotonicity between the distribution of winners from economic reform and the probability of its adoption. An increase in the number of winners may lower, rather than increase, the likelihood of adoption of economic reform. In particular, even though reforms that benefit a minority or an overwhelming majority are adopted, reforms that benefit a smaller majority are not adopted.